The Effect of Distillation on Ethanol Content in Sageru and Sopi Samples from Enau Trees (Arenga Pinnata) Using UV-Vis Spectrophotometer - Tabalessy, Oliviane Katherina; Santi, Santi (Helium: Journal of Science and Applied Chemistry, 2024)
Sopi is a traditional Maluku alcoholic drink produced from the fermentation of sageru from tapping palm trees (Arenga pinnata), one of the ingredients of which is ethanol. The research aimed to determine the ethanol content of sageru and beef samples from traditional and steam distillation. This experimental research method uses the UV-Vis spectrophotometer method to determine the effect of distillation on ethanol levels in sageru and sopi samples from Enau trees (Arengan pinnata). Based on the results of the quantitative analysis carried out using the UV-Vis spectrophotometry method, it was found that the alcohol content in traditional drinks (sageru and sopi) from palm plants (Arenga pinnata) was (13%-29%), which falls within the provisions of BPOM RI No. 6 of 2018 states that drinks that have ethyl alcohol or ethanol levels of more than 20% to 50% are included in group C. So, it can be concluded that the ethanol content was obtained in the sageru sample resulting from distillation at a temperature of 50 ºC to 78 ºC (13% - 27%). Ethanol levels were found in samples of traditional distilled beef (24% - 29%).